STUDI SUVENIR BERUKIR DI NAGARI PANDAI SIKEK KECAMATAN X KOTO KABUPATEN TANAH DATAR - JOHAN DWIPA MAHARDIKA, Drs. Efrizal, M.Pd., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2018)
Reseach aim to describe typical souvenir type of Pandai Sikek, formand carved name, then explain about ingredients and tool. Reseachuses qualitative and descriptive methods, by observation, interview,and documentation. The data analysis is done by data collection, datareduces, data presentation, and conclusion. Data validity tested withtriangulation technique. Reseach result found five types of typicalsouvenir products Pandai Sikek. On the five forms of souvenirsfound nine motifs names of seven traditional Minangkabau carvingpatterns. The typical souvenir products of Pandai Sikek made ofSurian wood, in the process using a Layang chisel and Sodok chisel.Kata Kunci : Suvenir, Pandai Sikek, Ukiran, Bahan dan Alat